2007
DOI: 10.1038/oby.2007.201
|View full text |Cite
|
Sign up to set email alerts
|

Baroreflex Sensitivity in Obesity: Relationship With Cardiac Autonomic Nervous System Activity

Abstract: [1685][1686][1687][1688][1689][1690][1691][1692][1693]. Objective: The aim of this study was to test the hypothesis that baroreflex sensitivity (BRS), assessed by indirect measurement of aortic pressure, is blunted in obesity. Additionally, the potential effect of cardiac autonomic nervous system (ANS) activity, aortic compliance, and metabolic parameters on BRS of obese subjects was investigated. Research Methods and Procedures:A group of 30 women with BMI Ͼ30 kg/m 2 and a group of 30 controls with BMI Ͻ25 kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
97
0
7

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(110 citation statements)
references
References 47 publications
6
97
0
7
Order By: Relevance
“…Previous studies observed an association between BMI and sympathetic activation (1,2,29). However, BMI may not be a valid measure to describe body composition because it does not distinguish between body fat and lean body mass.…”
Section: Tablementioning
confidence: 99%
“…Previous studies observed an association between BMI and sympathetic activation (1,2,29). However, BMI may not be a valid measure to describe body composition because it does not distinguish between body fat and lean body mass.…”
Section: Tablementioning
confidence: 99%
“…The depression of baroreceptor reflex sensitivity during weight gain in humans (4,21) is replicated in animal models of obesity (9,24,25,39,40). Furthermore, the restoration of baroreflex function with weight loss suggests a dynamic interrelationship between diet, metabolic status, and cardiovascular autonomic control (4,21,41,42). Obesity not only increases sympathetic outflow (SNS) to muscle (1,21) and kidneys (45), but it also decreases cardiac parasympathetic (PNS) drive (6,36).…”
mentioning
confidence: 99%
“…10 Blunted BRS in obese animals and humans also represents a negative prognostic factor in cardiovascular diseases and may lead to long-term cardiovascular mortality. 7,34 The development of blunted BRS in obesity is insidious and may often be overlooked because patients are typically free of complaints. Our current finding that the blunted BRS in obese Zucker rats is, at least in part, attributed to altered nitroxidergic or NMDA receptor-mediated modulation provides a possible explanation for the development of blunted BRS in obesity.…”
Section: Significancementioning
confidence: 99%
“…1 The impulses triggered by arterial baroreceptors are propagated through the glossopharyngeal and vagus nerves to the nucleus tractus solitarii of the medulla, resulting in inhibition of the sympathetic system and activation of the parasympathetic system. [3][4] Baroreflex sensitivity (BRS) has often been reported to be impaired or reduced in normotensive obese subjects, 5 hypertensive patients with central obesity, 6 obese women, 7 young and older obese men, 8 and obese patients with metabolic syndrome. 9 The underlying mechanism of baroreflex attenuation in obesity is not yet well known; however, there is increasing evidence that it is at least partly related to autonomic nervous system dysfunction and particularly to the sympathetic overactivity that accompanies obesity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation